Knowledge and skills requirements of National University of Lesotho librarians in meeting information needs of humanities undergraduate students in the digital age - Nkuebe, Mantoetse Pontso Alice (Library and Information Studies Centre (LISC), 2017)
This study attempted to ascertain what knowledge and skills are required for NUL librarians to meet the information needs of humanities undergraduate students in the digital era academic library environment. To address the objective of this study, the following research questions were generated: what are the library related information needs of NUL humanities undergraduate students in the current digital age?; what knowledge and skills are required of NUL librarians in meeting the library related information needs of humanities undergraduate students in the current digital age?; to what extent has technology affected the roles and functions of NUL academic librarians?; to what extent are NUL librarians readily adapting to and embracing technological changes affecting academic library resources and services?; and, what type of education and training are required for NUL librarians to effectively meet the information needs of humanities undergraduate students in the digital age academic library environment? The study was supported by organizational learning theory. It employed a convergent parallel mixed methods approach within a pragmativist paradigm for the collection of both quantitative and qualitative data to respond to the research questions guiding the study. A case study design was adopted in identifying humanities undergraduate students' information needs and concurrently ascertaining knowledge and skills requirements of NUL librarians. The target population included NUL librarians and humanities undergraduate students. Non-probability purposive sampling was employed to collect qualitative data (from the librarians) whist probability stratified random sampling was adopted to obtain quantitative data (from humanities undergraduate students). Data were collected via face-to-face semi-structured interviews with librarians and a structured questionnaire for students. In concluding, the study presents, inter alia, a blend of required disciplinary, generic and personal competencies for NUL librarians to meet the library related information needs of humanities undergraduate students in the current digital age. It recommends, inter alia, the adoption of effective organizational learning to build on NUL librarian's existing knowledge and skills so that they may more easily adapt to rapidly evolving technology and more fully meet the information needs of humanities undergraduate students.